2022
DOI: 10.1088/0256-307x/39/7/077401
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Quasi-two-dimensional Superconductivity and Tunable Kondo Lattice in a van der Waals Superconductor

Abstract: Realization of Kondo lattice in superconducting van der Waals materials not only provides a unique opportunity for tuning the Kondo lattice behavior by electrical gating or intercalation, but also is helpful for further understanding the heavy fermion superconductivity. Here we report a low-temperature and vector-magnetic-field scanning tunneling microscopy and spectroscopy study on a superconducting compound (4Hb-TaS2) with alternate stacking of 1T-TaS2 and 1H-TaS2 layers. We observe the quasi-two-dimensional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(59 reference statements)
0
8
4
Order By: Relevance
“…Recently, the emerging natural bulk TMD VDWHs that share configurations similar to those of 2D VDWHs are ideal systems suitable for such studies. They are alternately stacked with octahedral ( T ) layers with CDW order and trigonal-prismatic ( H ) layers with superconductivity and different CDW orders. Pressure is a clean, continuous, and reversible way to regulate the interlayer coupling by changing the interlayer distance without introducing any chemical impurities into VDWHs. , Pressure has also been broadly applied in bulk TMD systems to tune the electronic properties associated with the CDW states and superconductivity. …”
mentioning
confidence: 99%
“…Recently, the emerging natural bulk TMD VDWHs that share configurations similar to those of 2D VDWHs are ideal systems suitable for such studies. They are alternately stacked with octahedral ( T ) layers with CDW order and trigonal-prismatic ( H ) layers with superconductivity and different CDW orders. Pressure is a clean, continuous, and reversible way to regulate the interlayer coupling by changing the interlayer distance without introducing any chemical impurities into VDWHs. , Pressure has also been broadly applied in bulk TMD systems to tune the electronic properties associated with the CDW states and superconductivity. …”
mentioning
confidence: 99%
“…The superconductivity of 2D materials, such as the much-publicized magic-angle graphene [167], has aroused great interest in the field of physics. Shen et al demonstrated in their research on 4Hb-TaS 2 that the quasi 2D superconductivity in the 1H layer coexists with the Kondo resonance in the 1T layer, and the intensity of the Kondo resonance peak can be modulated by adjusting its relative position to the Fermi level [168].…”
Section: Tmd-based New Structure and New Working Principlementioning
confidence: 99%
“…The role of these new bands in superconductivity is not clear. It has been suggested that Kondo physics seen in 4Hb 22,23 and in 1T/1H bilayers 13 could be related to these narrow bands.…”
mentioning
confidence: 99%